Assessment of myocardial function in preterm infants with patent ductus arteriosus using tissue Doppler imaging. (16th October 2013) - Parikh, Ravikumar; Negrine, Robert J. S.; Chikermane, Ashish; Rasiah, Shree Vishna; Ewer, Andrew K.
Abstract Objective: To assess myocardial function in preterm infants with different degrees of ductal patency in the first week of life using tissue Doppler imaging. Study design: Infants <30 weeks of gestation underwent echocardiography on day 3. A total of 72 infants were recruited into the study and categorised into three groups (i) haemodyamically significant ductus arteriosus, (ii) patent ductus arteriosus and (iii) no patent ductus arteriosus. Those with haemodynamically significant ductus arteriosus were treated with indometacin and echocardiography was repeated after 48–72 hours following treatment. Peak systolic and diastolic myocardial velocities were obtained using tissue Doppler imaging, and myocardial performance index was calculated. Results: Initial myocardial velocities were significantly lower and myocardial performance index significantly higher in the haemodynamically significant ductus arteriosus group compared with other groups. For the haemodynamically significant ductus arteriosus group, post-treatment myocardial velocities were higher and myocardial performance index lower than pre-treatment. Conclusion: Preterm infants with haemodynamically significant ductus arteriosus had lower myocardial velocities and higher myocardial performance index, suggesting relative systolic and diastolic myocardial dysfunction. Babies whose patent ductus arteriosus remained open despite indometacin had lower pre-treatment myocardial velocities and higher myocardial performance index than those babies whose patent ductus arteriosus closed, suggesting worse myocardial function in this group. Measurement of myocardial function using tissue Doppler imaging in preterm infants is feasible and may prove to be helpful in the management of babies with patent ductus arteriosus.